8 Ways to Boost Students Engagement During Asynchronous English Language Learning - Nurkarimah, Yusof (UMPSA, 2025)
Imagine a classroom unbound by walls where students are free to learn whenever, wherever and however they choose. In today’s digital age, this is exactly what asynchronous learning offers students. For some students, asynchronous learning is the ultimate game-changer, as it offers flexibilities and new learning opportunities such as self-paced learning. On the other hand, some students may face challenges, particularly in maintaining their motivation and self-discipline to learn, for example in language courses such as English, without direct face-to-face interactions during this learning mode.